Strategic Planning for Poverty Reduction in Vietnam : Progress and Challenges for Meeting the Localized Millennium Development Goals - Swinkels, Rob; Turk, Carrie (World Bank, Washington, DC, 2014)
This paper discusses the progress that Vietnam has made toward meeting a core set of development goals that the government recently adopted as part of its Comprehensive Poverty Reduction and Growth Strategy (CPRGS). These goals are strongly related to the Millennium Development Goals (MDGs), but are adapted and expanded to reflect Vietnam's national challenges and the government's ambitious development plans. For each Vietnam Development Goal, the authors describe recent trends in relation to the trajectories implied by the MDGs, outline the intermediate targets identified by the government, and discuss the challenges involved in meeting these. Relative to other countries of similar per capita expenditures, Vietnam has made rapid progress in a number of key areas. Poverty has halved over the 1990s, enrollment rates in primary education have risen to 91 percent (although there is a quality problem), indicators of gender equity have been strengthened, child mortality has been reduced, maternal health has improved, and real progress has been made in combating malaria and other communicable diseases. In contrast, Vietnam scores worse than other comparable countries in the areas of child malnutrition, access to clean water, and combating HIV/AIDS. A number of important crosscutting issues emerge from this analysis that need to be addressed. One such challenge is improving equity, both in terms of ensuring that the benefits of growth are distributed evenly across the population and in terms of access to public services. This will involve addressing the affordability of education and curative health care for poor households. Improvements in public expenditure planning are needed to align resources better to stated desired outcomes and to link nationally-defined targets to subnational planning and budgeting processes. There is also a need to address capacity and data gaps which will be crucial for effective monitoring.